The role of P2Y[subscript]2 nucleotide receptor in lipoprotein receptor-related protein 1 expression and aggregated low density lipoprotein uptake in vascular smooth muscle cells - Dissmore, Tixieanna (Kansas State University, 2012)
The internalization of aggregated low-density lipoprotein (agLDL) may involve the actin cytoskeleton in ways that differ from the endocytosis of soluble LDL. Based on previous findings the P2Y[subscript]2 receptor (P2Y[subscript]2R) mediates these effects through interaction with filamin‐A (FLN‐A), an actin binding protein. Our findings also showed that uridine 5’‐ triphosphate (UTP), a preferential agonist of the P2Y[subscript]2R, stimulates the uptake of agLDL, and increases expression of low‐density lipoprotein receptor related protein 1 (LRP 1) in cultured mouse vascular smooth muscle cells (SMCs). The strategy of this research was to define novel mechanisms of LDL uptake through the modulation of the actin cytoskeleton in order to identify molecular targets involved in foam cell formation in vascular SMCs. For this project, we isolated aortic SMCs from wild type (WT) and P2Y[subscript]2R‐/‐ mice to investigate whether UTP and the P2Y[subscript]2R modulate expression of LRP 1 and low‐density lipoprotein receptor (LDLR). We also investigated the effects of UTP on uptake of DiI‐labeled agLDL in WT and P2Y[subscript]2R‐/‐ vascular SMCs. For LRP1 expression, cells were stimulated in the presence or absence of 10 [mu]M UTP. To determine LDLR mRNA expression, and for agLDL uptake, cells were transiently transfected for 24 h with cDNA encoding hemagglutinin-tagged (HA-tagged) WT P2Y[subscript]2R or a mutant P2Y[subscript]2R that does not bind FLN‐A, and afterwards treated with 10 [mu]M UTP. Total RNA was isolated, reversed transcribed to cDNA, and mRNA relative abundance determined by RT-PCR using the delta-delta Ct method with GAPDH as control gene. Results show SMCs expressing the mutant P2Y[subscript]2R that lacks the FLN‐A binding domain exhibit 3‐fold lower LDLR expression than SMCs expressing the WT P2Y[subscript]2R. There was also decrease in LRP1 mRNA expression in response to UTP in P2Y[subscript]2R‐/‐ SMCs compared to WT. Actinomycin‐D (20 [mu]g/ml) significantly reduced UTP-induced LRP1 mRNA expression in P2Y[subscript]2R‐/‐ SMCs (P < 0.05). Compared to cells transfected with mutant P2Y[subscript]2R, cells transfected with WT P2Y[subscript]2R showed greater agLDL uptake in both WT VSMC and P2Y[subscript]2R-/- cells. Together these results show that both LRP 1 and LDLR expressions are dependent on an intact P2Y[subscript]2R, and P2Y[subscript]2R/ FLN‐ A interaction is necessary for agLDL uptake.
Keywords: P2Y[subscript]2 receptor and regulation of low-density lipoprotein receptor related protein; P2Y[subscript]2R-FLN-A interaction and aggregated low-density lipoprotein uptake; Uridine triphosphate induced aggregated low-density lipoprotein uptake; Actin cytoskeleton reorganization in low-density lipoprotein uptake; P2Y[subscript]2R/FLN-A interaction and foam cell formation; P2Y[subscript]2R/FLN-A interaction, LRP1 expression and atherogenesis; Molecular Biology (0307); Nutrition (0570)